Documenter la crise agraire haïtienne sous la dictature duvaliériste - Adeline Bouvard; Ariane Degroote (EchoGéo)
At the end of the 1970s, against a backdrop of dictatorship and extreme poverty in rural Haiti, Canadian film-makers Gérald and Paule Belkin set up a "video communication" project to shed light on the Haitian agrarian crisis. The project is taking place in a small region of the country where a rural development project run by the French cooperation began a few years ago. This article analyses the audiovisual approach adopted by the Belkin and how it relates to this development project, based on the close involvement of the region's farmers. While the agricultural development project in Salagnac enabled, facilitated the Belkin's work and gave a wider scope to the farmers' words and to their reflections on development and the agrarian crisis in the region. Since the 1980s, the Belkin's audiovisual approach has also been one of the pioneers of more horizontal communication, involving rural farming communities.